Growth Deficiencies of Neisseria meningitidis pfs and luxS Mutants Are Not Due to Inactivation of Quorum Sensing - Heurlier, Karin (American Society for Microbiology (ASM), 2009)
The activated methyl cycle (AMC) is a central metabolic pathway used to generate (and recycle) several important metabolites and enable methylation. Pfs and LuxS are considered integral components of this pathway because they convert S-adenosylhomocysteine (SAH) to S-ribosylhomocysteine (SRH) and S-ribosylhomocysteine to homocysteine (HCY), respectively. The latter reaction has a second function since it also generates the precursor of the quorum-sensing molecule autoinducer 2 (AI-2). By demonstrating that there was a complete lack of AI-2 production in pfs mutants of the causative agent of meningitis and septicemia, Neisseria meningitidis, we showed that the Pfs reaction is the sole intracellular source of the AI-2 signal. Analysis of lacZ reporters and real-time PCR experiments indicated that pfs is expressed constitutively from a promoter immediately upstream, and careful study of the pfs mutants revealed a growth defect that could not be attributed to a lack of AI-2. Metabolite profiling of the wild type and of a pfs mutant under various growth conditions revealed changes in the concentrations of several AMC metabolites, particularly SRH and SAH and under some conditions also HCY. Similar studies established that an N. meningitidis luxS mutant also has metabolite pool changes and growth defects in line with the function of LuxS downstream of Pfs in the AMC. Thus, the observed growth defect of N. meningitidis pfs and luxS mutants is not due to quorum sensing but is probably due to metabolic imbalance and, in the case of pfs inactivation, is most likely due to toxic accumulation of SAH.